UPAYA MENINGKATKAN FEELING OF INFERIORITY MELALUI KONSELING INDIVIDUAL DIPANTI ASUHAN MANDEH KANDUANG - Syakila Errina Fitri; Dodi Pasilaputra (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This research is entitled efforts to increase feelings of inferiority through individual counseling in the Mendeh Kanduang orphanage where clients who have symptoms that appear to lack self-confidence, tend to close themselves off and withdraw from the environment both in the school environment and in the family environment in the orphanage, as well as Excessive worry is motivated by a lack of love from parents, making the counselee afraid of not getting love from their parents or those around them. Therefore, counselors provide assistance to clients who are affected by feelings of inferiority. The aim of this research is to find out how counselors try to overcome feelings of inferiority, namely through individual counseling services. Individual counseling is carried out in order to find out the problems that occur in the counselee. The research method used is descriptive qualitative, to describe the counselor's efforts to overcome feelings of inferiority through individual counseling. This research uses data collection techniques through interviews and documentation obtained from the counselees, orphanage mothers and friends of the counselees in the orphanage.